(untitled) (Costos y Gestión, 2021)
Critical alterations of the characteristic variables of a business environment challenge any of the business models designed. But, an alternative to manage it is to access other rings beyond the reduced environment, to generate business anchors permanently or temporarily. The global debacle of environments, such as the one unleashed by the health crisis due to the impact of the COVID-19 pandemic, seems to leave no space to generate these anchors and expose business models to their reconversion. Meanwhile, the challenge is to survive and optimize all the resources available to the decision maker. The confrontation between business models with full vertical integration, as opposed to those with a satellite structure of autonomous cells, has fed the concept of building “light” businesses in terms of fixed costs of capacity and operation, with the consequent minimization of capital investment and the immobilization of working capital. However, many of the arguments outlined during the first months of the COVID-19 pandemic, advocate favoring vertical integration as a common factor for those companies that most firmly resist the impact of imbalances in the matrix “supplies–products-market” The objective of this work is to analyze the lightness factors in a proposal related to a matrix analysis structure, identifying the costs derived from the collateral effects of such lightweight structure and the counterpoint with those businesses that need vertical integration to differentiate themselves in the scenario post-pandemic COVID-19.